Biallelic variants in ZNF526 cause a severe neurodevelopmental disorder with microcephaly, bilateral cataract, epilepsy and simplified gyration. Issue 3 (4th January 2021) - Dentici, Maria Lisa; Alesi, Viola; Quinodoz, Mathieu; Robens, Barbara; Guerin, Andrea; Lebon, Sébastien; Poduri, Annapurna; Travaglini, Lorena; Graziola, Federica; Afenjar, Alexandra; Keren, Boris; Licursi, Valerio; et al.
Abstract : Background: Next-generation sequencing, combined with international pooling of cases, has impressively enhanced the discovery of genes responsible for Mendelian neurodevelopmental disorders, particularly in individuals affected by clinically undiagnosed diseases. To date, biallelic missense variants in ZNF526 gene, encoding a Krüppel-type zinc-finger protein, have been reported in three families with non-syndromic intellectual disability. Methods: Here, we describe five individuals from four unrelated families with an undiagnosed neurodevelopmental disorder in which we performed exome sequencing, on a combination of trio-based (4 subjects) or single probands (1 subject). Results: We identified five patients from four unrelated families with homozygous ZNF526 variants by whole exome sequencing. Four had variants resulting in truncation of ZNF526; they were affected by severe prenatal and postnatal microcephaly (ranging from −4 SD to −8 SD), profound psychomotor delay, hypertonic–dystonic movements, epilepsy and simplified gyral pattern on MRI. All of them also displayed bilateral progressive cataracts. A fifth patient had a homozygous missense variant and a slightly less severe disorder, with postnatal microcephaly (−2 SD), progressive bilateral cataracts, severe intellectual disability and unremarkable brain MRI. Mutant znf526 zebrafish larvae had notable malformations of the eye and central nervous system, resembling findings seen in the human holoprosencephaly spectrum. Conclusion: Our findings support the role of ZNF526 biallelic variants in a complex neurodevelopmental disorder, primarily affecting brain and eyes, resulting in severe microcephaly, simplified gyral pattern, epileptic encephalopathy and bilateral cataracts.